An observational study of shift length, crew familiarity, and occupational injury and illness in emergency medical services workers. Issue 11 (14th September 2015) - Weaver, Matthew D; Patterson, P Daniel; Fabio, Anthony; Moore, Charity G; Freiberg, Matthew S; Songer, Thomas J
Abstract : Objectives: Emergency medical services (EMS) clinicians are shift workers deployed in two-person teams. Extended shift duration, workplace fatigue, poor sleep and lack of familiarity with teammates are common in the EMS workforce and may contribute to workplace injury. We sought to examine the relationship between shift length and occupational injury while controlling for relevant shift work and teamwork factors. Methods: We obtained 3 years of shift schedules and occupational injury and illness reports were from 14 large EMS agencies. We abstracted shift length and additional scheduling and team characteristics from shift schedules. We matched occupational injury and illness reports to shift records and used hierarchical logistic regression models to test the relationship between shift length and occupational injury and illness while controlling for teammate familiarity. Results: The cohort contained 966 082 shifts, 4382 employees and 950 outcome reports. Risk of occupational injury and illness was lower for shifts ≤8 h in duration (RR 0.70; 95% CI 0.51 to 0.96) compared with shifts >8 and ≤12 h. Relative to shifts >8 and ≤12 h, risk of injury was 60% greater (RR 1.60; 95% CI 1.22 to 2.10) for employees that worked shifts >16 and ≤24 h. Conclusions: Shift length is associated with increased risk of occupational injury and illness in this sample of EMS shift workers.